THE EFFECT OF HIIT (HIGH INTENSITY INTERVAL TRAINING) TRAINING ON THE MUSCLE STRENGTH OF THE UPPER BODY OF FK UNDIP STUDENTS - Stanley, Marvin; Kumaidah, Endang; Adji, Raden Mas Soerjo; Sumardi, Widodo (Diponegoro International Medical Journal, 2024)
Background: High-Intensity Interval Training (HIIT) is a form of physical training characterized by its high intensity, faster speed than regular physical training, and faster recovery speed. High-Intensity Interval training is often used by athletes because of its potent effect in increasing muscle growth and promoting health. The upper limb muscles are often used on a day to day basis. This research was conducted to find out the effectiveness of HIIT training in developing the upper body muscles.Objective: To determine the effectiveness of HIIT in developing the upper body muscles.Methods: The research is quasi experimental, with pre-test and post-test control group, with 2 participating groups, which are the sample group and the control group. The independent variable of the research is High-Intensity Interval Training, while the dependent variable is upper body muscle strength.Result: Based on the study, High Intensity Interval Training that focuses on the upper body muscles has a significant correlation with the upper body strength of Diponegoro University Medical College students. The treatment group showed an increase in throw distance during the SMBT, while the control group showed stagnating and decreasing throw distance.Conclusion: High-Intensity Interval Training is proven to be an effective exercise to increase upper-body strength on Diponegoro University Students.Keywords: High-Intensity Interval Training, Upper body muscle strength.